The addition of PD-1/PD-L1 axis blockade to BRAF and MEK inhibition for advanced melanoma patients harboring BRAF mutations: a systematic review and meta-analysis - Mauricio Fernando Silva Almeida Ribeiro; Camila Bragança Xavier; Allan Andresson Lima Pereira; Mariana Scaranti; Luiza Dib Batista Bugiato Faria; Tatiana Strava Correa; Marina Sahade; David Queiroz Borges Muniz; Olavo Feher; Gustavo dos Santos Fernandes; Artur Katz; Rodrigo Ramella Munhoz (Brazilian Journal of Oncology, 2022)
Objectives: Immune-checkpoint inhibitors (ICI) and targeted-therapies (TT) have become standard options for BRAF-V600 metastatic melanomas (MM). Recently, randomized trials (RCT) addressed the efficacy of combined approaches, with conflicting results. We sought to evaluate efficacy and safety of first-line combination ICI and BRAF/MEK inhibitors (triplets) versus BRAF/MEKi (doublets).